The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s11581-011-0573-z
|View full text |Cite
|
Sign up to set email alerts
|

Role of mesopores on the electrochemical performance of LiCoO2 composite cathodes for lithium ion batteries

Abstract: Mesoporous carbon (MC) was utilized to increase the mesoporosity of LiCoO 2 composite cathode. Graphite powder (GP) was chosen as a standard of comparison because of its very low mesoporosity. Compared with MC, GP has similar particle size, lower specific surface area, and higher electronic conductivity. Acetylene black (AB) exists in the form of chains of nanoparticles. With all other factors held constant, the mixture of AB and MC (ABMC)-loaded LiCoO 2 composite cathode (ABMC cathode) was superior to the mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Such approaches yield easy access to effective characteristics of the composite as a whole, e.g., specific energy density, capacity retention, or cycle lifetime. However, as the interplay of material components and the microstructure of the composite electrode determine its effective properties, the individual contributions of its components or of interfaces and interphases formed between them cannot be easily separated. Little can be learned about the intrinsic properties of the CAM within the composite electrode, e.g., effects of size of primary and secondary CAM particles or of network formation.…”
mentioning
confidence: 99%
“…Such approaches yield easy access to effective characteristics of the composite as a whole, e.g., specific energy density, capacity retention, or cycle lifetime. However, as the interplay of material components and the microstructure of the composite electrode determine its effective properties, the individual contributions of its components or of interfaces and interphases formed between them cannot be easily separated. Little can be learned about the intrinsic properties of the CAM within the composite electrode, e.g., effects of size of primary and secondary CAM particles or of network formation.…”
mentioning
confidence: 99%
“…It was found that the dramatically lowered R ct values after 3 charge/discharge cycles in meso-LiFePO 4 material reduced the polarization 21 and provided lithium ions a buffer for quick electrochemical reactions. 12 In addition, the meso-material architecture remarkably reduced the R ct values, 81.5 for Sample A and 17.7 for Sample B, which are an order smaller than those reported previously (210 with ferrous 44 and 255 with ferric, 16 and resulted in fast electronic transport.…”
Section: Resultsmentioning
confidence: 66%
“…For example, nanoparticles or nanorods and porous structures could significantly enhance reaction kinetics in electrode materials, 2,3 while nanoporous spherical particles, 4,5 mesoporous nanoparticles, [6][7][8][9] hierarchical porous composite 10 and dual-porosity composite 11 exhibited a high rate capability and capacity retention upon cycling in LiFePO 4 /C. Owing the advantages of nano or porous structures, good electrochemical performances could be achieved in LiCoO 2 , 12 LiMn 2 O 4 , 13 Li 2 MnSiO 4 , 14 Li 2 FeSiO 4 [15][16][17] cathode materials and some anode materials. [18][19][20] It has been suggested that the effectively improved penetration of electrolyte with the mesoporous composites could enhance the diffusion of lithium ions because of a reduced transport length, which makes a better accommodation of strain during lithium intercalation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A C C E P T E D ACCEPTED MANUSCRIPT 2 After dominating portable power source for cell phone, digital camera, laptop, tablet computer, and so on, lithium ion batteries (LIBs) have already emerged as the prime new energy devices for electric vehicles, hybrid electric vehicles and energy storage due to their high energy density, large rate capability, long cycle life as well as environmental benign [1][2][3][4][5][6]. These ever increasing applications of LIBs promote the urgent demand for electrode materials with both high capacity and rate capability.…”
Section: A N U S C R I P Tmentioning
confidence: 99%